Tracking development assistance for HIV/AIDS: the international response to a global epidemic - Schneider, Matthew T. (AIDS, 2016)
To better understand the global response to HIV/AIDS, this study tracked development assistance for HIV/AIDS at a granular, program level. METHODS: We extracted data from the Institute for Health Metrics and Evaluation's Financing Global Health 2015 report that captured development assistance for HIV/AIDS from 1990 to 2015 for all major bilateral and multilateral aid agencies. To build on these data, we extracted additional budget data, and disaggregated development assistance for HIV/AIDS into nine program areas, including prevention, treatment, and health system support. RESULTS: Since 2000, $109.8 billion of development assistance has been provided for HIV/AIDS. Between 2000 and 2010, development assistance for HIV/AIDS increased at an annualized rate of 22.8%. Since 2010, the annualized rate of growth has dropped to 1.3%. Had development assistance for HIV/AIDS continued to climb after 2010 as it had in the previous decade, $44.8 billion more in development assistance would have been available for HIV/AIDS. Since 1990, treatment and prevention were the most funded HIV/AIDS program areas receiving $24.6 billion and $22.7 billion, respectively. Since 2010, these two program areas and HIV/AIDS health system strengthening have continued to grow, marginally, with majority support from the US government and the Global Fund. An average of $252.9 of HIV/AIDS development assistance per HIV/AIDS prevalent case was disbursed between 2011 and 2013. CONCLUSION: The scale-up of development assistance for HIV/AIDS from 2000 to 2010 was unprecedented. During this period, international donors prioritized HIV/AIDS treatment, prevention, and health system support. Since 2010, funding for HIV/AIDS has plateaued.